2008
DOI: 10.1016/j.juro.2007.10.051
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Obstruction Induced Overactive Bladder Symptoms Following Urethrolysis for Female Bladder Outlet Obstruction

Abstract: Following urethrolysis overactive bladder symptoms may remain refractory in 50% or greater of patients, which has a negative impact on quality of life and the impression of improvement after surgery. Detrusor overactivity demonstrated preoperatively may be useful for predicting who may have persistent overactive bladder symptoms despite an effective urethrolysis procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 20 publications
2
24
1
Order By: Relevance
“…The study evaluated 40 patients with obstructive urinary symptoms, 36 of whom reported OAB symptomatology at presentation. After urethrolysis, 56 % reported refractory OAB and were continued on antimuscarinics post-operatively, with 8 ultimately undergoing sacral neuromodulation [57,58]. As such, prompt diagnosis of BOO and early intervention is prudent.…”
Section: Bladder Outlet Obstructionmentioning
confidence: 99%
“…The study evaluated 40 patients with obstructive urinary symptoms, 36 of whom reported OAB symptomatology at presentation. After urethrolysis, 56 % reported refractory OAB and were continued on antimuscarinics post-operatively, with 8 ultimately undergoing sacral neuromodulation [57,58]. As such, prompt diagnosis of BOO and early intervention is prudent.…”
Section: Bladder Outlet Obstructionmentioning
confidence: 99%
“…Compared with obstructive symptoms such as hesitancy, straining, and poor force of stream, overactive bladder symptoms caused by iatrogenically induced BOO following anti-incontinence surgery are less likely to improve despite a technically successful operation. In one series, voiding symptoms resolved in 82 % of obstructed patients following urethrolysis while OAB (storage) symptoms resolved in only 35 % [ 37 ]. In this series, increased time to intervention was not correlated with persistent detrusor dysfunction.…”
Section: Postoperative Complications Voiding Dysfunction and Urinary mentioning
confidence: 62%
“…15,19 In a retrospective series of 40 patients who underwent urethrolysis, Starkman et al reported that OAB may remain refractory in 50% of patients or more, and this had a negative impact on quality of life and the impression of improvement after surgery in their study. 20 In our experience, in patients with refractory OAB symptoms prior to surgery, if BOO has resolved following surgery, persistent OAB symptoms typically respond to cholinolytic therapy or onabotulinum toxin-A injection. In other words, relief of the BOO may turn treatment-refractory storage symptoms or UUI into a treatment-responsive condition.…”
Section: Discussionmentioning
confidence: 91%
“…Ten of 11 patients had evaluable pressure flow studies. Median preoperative intubated peak flow rate and maximum detrusor pressure during voiding were 7.5 cc/s (range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], and 16 cm Among the three patients who complained of SUI preoperatively, SUI resolved in two patients and one patient complained of persistent SUI following SMUM, but this occurred rarely and did not require the use of any protection. One patient (9%) developed recurrent SUI and is planned to undergo periurethral bulking injection.…”
Section: Resultsmentioning
confidence: 99%